Robotics for enhancing independent living skills in adolescents and young adults with autism spectrum disorder: a systematic review (Research, Society and Development, 2021)
This is a review of studies from the years 2010 to 2021 on the use of robotics to improve the independent living skills of adolescents and young adults with autism spectrum disorder (ASD). Individuals with ASD experience a wide range of challenges, including difficulties in social functioning, one of the core features of the disorder. Rapid progress in technology during recent years, especially in the field of robotics, offers new possibilities of training and education for individuals with ASD. This review addresses specific research questions on the use of robotics in ASD, related to the characteristics of the participants, skills, settings, technologies, data collection methods, evaluation parameters, intervention outcomes, generalization, maintenance, and research rigor. Social skills were the main target in the interventions for adolescents and young adults with ASD. Most of the studies reviewed used questionnaires, and observation as the data collection methods, and the classroom environment and a controlled research environment were the most common settings. Most of the evaluation parameters included the frequency, duration, and number of specific responses. All the studies in the review reported positive results in independent living skills of young people with ASD, but none had conducted generalization and/or maintenance probes. In terms of research rigor, the studies were generally rated as having adequate strength. Robotics appears to be an intervention that shows potential for the enhancement of independent living skills of adolescents and young adults with ASD. Future research should focus on the improvement of work-related social skills of adolescents and young adults with ASD. Exploration of the generalization and the maintenance of the acquired skills should be part of the study protocol.